Factor Analysis of Tax Knowledge, Firmness of Sanctions, and Fairness of MSME Tax Compliance in Garut Regency - Nurlaela, Lina; Syakinah, Fitri (Moneta : Journal of Economics and Finance, 2024)
MSMEs are critical to Indonesia’s economic framework, yet their compliance with tax regulations has been a persistent challenge. Therefore, the researcher seeks to uncover how tax literacy, tax penalty rates, and perceptions of tax fairness impact tax compliance of micro, small, and medium enterprises (MSMEs) at KPP Pratama Garut. This paper brings a new perspective to existing research by focusing specifically on the MSME sector in Garut Province. This area is under-researched in the context of tax compliance. The method used is quantitative. Data collection uses questionnaires sent to taxpayers. The sample used is purposive sampling. The participant group comprises micro, small, and medium enterprise taxpayers who have submitted annual tax returns to KPP Pratama Garut, have a Taxpayer Identification Number (NPWP), and are registered as taxpayers. Thirty eligible individuals participated in this study, including residents of Garut Province. Tax subjects with a Taxpayer Identification Number (NPWP): Taxpayers with assets of at least 500,000,000 rupiahs companies based on their size are divided into several categories, namely MSMEs. This study uses descriptive and quantitative methods. Tax compliance of MSME actors at KPP Pratama Garut is not necessarily related to tax expertise but is closely related to tax sanctions and tax fairness. Three main factors influence the tax compliance of MSME actors at KPP Pratama Garut: 1) the severity of sanctions,2) tax knowledge, and 3) tax fairness.